A New Form of the Co-Housing Open Space Concept Application for Low-Income Community Housing in the New-Normal Era which Environmentally Friendly - Ina Triesna Budiani; Sasmita Siregar; Aulia Muflih Nst; Yunita Syafitri Rambe (International Journal of Architecture and Urbanism, 2026)
Along with the narrowness of urban land and the more expensive, it is making people in dense cities who live more in slum areas require alternative solutions to the problem of providing houses with open spaces that be used together but which are affordable and environmentally friendly, incredibly energy efficient. Co-Housing is a concept where a community group plans, finances, and builds their house together on the same land/parcel and has communal/shared spaces . The concept of Co-housing is usually applied in new housing, but given the high price of land in dense cities, this concept will be tried to be used to housing in existing slums. Where a group of people's houses are revitalized and equipped with communal/shared open spaces that are environmentally friendly, especially energy efficient so that people do not have to spend a lot of money to get all the existing facilities available in these communal/shared open spaces. The purpose of this research was to create a new form of the Co-Housing Concept of open shared spaces in environmentally friendly low-income housing. The research method used was descriptive qualitative, which was supported by the identification of land for the Co-Housing concept application and city regulations. The result of the research was a layout draft (master plan) of a new concept of open shared spaces in environmentally friendly low-income housing in several dense urban slum areas.